How To Do Things With Books: Steve Tomasula’s VAS, an Opera in Flatland - Tissut, Anne-Laure (Sens public)

(untitled) (Département des littératures de langue française, 2021)
The multimedia pages of VAS are a continuing exploration of forms of representation, which concomitantly show how meaning is constructed. In so doing, both the modalities of reading and our relationship to the book itself are radically challenged. This article shows how VAS revisits the standards of the book, in both its conception and reception, by revealing the political, economic and social, but also philosophical and even ethical issues related to these norms.